Distributed Absorber for Noise and Vibration Control - Michel Azoulay; Alexander Veprik; Vladimir Babitsky; Neil Halliwell (Shock and Vibration)
An approach to a wide-band frequency passive vibration attenuation is introduced in this paper. This aims to suppress noise and vibration of extended multimode objects like plates, panels and shells. The absorber is arranged in the form of a single-layer assembly of small inertial bodies (balls) being distributed and moulded within the light visco-elastic media (e.g. silicone resin). The absorber as a whole is embedded into object face covering the critical patches of the system surface. For the purpose of characterization, the authors introduced the complex frequency response function relating the volume velocity produced by the vibrating object surface (response) stimulated by a point-wise force (stimulus) applied to a particular point. The simulation and optimization of the main frequency characteristics has been performed using a full scale 3-dimensional Finite Element model. These revealed some new dynamic features of absorber's structures, which can contribute to vibration attenuation. A full-scale physical experimentation with synthesised absorber's structures confirmed the main results of simulation and has shown significant noise reduction over a staggering 0–20 kHz frequency band. This was achieved with a negligible weight and volume penalty due to the addition of the absorber. The results can find multiple applications in noise and vibration control of different structures. Some examples of such applications are presented.